Tenant-Based Housing Voucher Programs: A Community Guide Systematic Review. Issue 6 (8th November 2022) - Finnie, Ramona K. C.; Peng, Yinan; Hahn, Robert A.; Schwartz, Alex; Emmons, Karen; Montgomery, Ann Elizabeth; Muntaner, Carles; Garrison, Veronica Helms; Truman, Benedict I.; Johnson, Robert L.; Fullilove, Mindy T.; Cobb, Jamaicia; et al.
Abstract : Context: Unaffordable or insecure housing is associated with poor health in children and adults. Tenant-based housing voucher programs (voucher programs) limit rent to 30% or less of household income to help households with low income obtain safe and affordable housing. Objective: To determine the effectiveness of voucher programs in improving housing, health, and other health-related outcomes for households with low income. Design: Community Guide systematic review methods were used to assess intervention effectiveness and threats to validity. An updated systematic search based on a previous Community Guide review was conducted for literature published from 1999 to July 2019 using electronic databases. Reference lists of included studies were also searched. Eligibility Criteria: Studies were included if they assessed voucher programs in the United States, had concurrent comparison populations, assessed outcomes of interest, were written in English, and published in peer-reviewed journals or government reports. Main Outcome Measures: Housing quality and stability, neighborhood opportunity (safety and poverty), education, income, employment, physical and mental health, health care use, and risky health behavior. Results: Seven studies met inclusion criteria. Compared with low-income households not offered vouchers, voucher-using households reported increased housing quality (7.9 percentage points [pct pts]), decreased housing insecurity or homelessness (−22.4 pct pts), and decreased neighborhood poverty (−5.2 pct pts). Adults in voucher-using households had improved health care access and physical and mental health. Female youth experienced better physical and mental health but not male youth. Children who entered the voucher programs under 13 years of age had improved educational attainment, employment, and income in their adulthood; children's gains in these outcomes were inversely related to their age at program entry. Conclusion: Voucher programs improved health and several health-related outcomes for voucher-using households, particularly young children. Research is still needed to better understand household's experiences and contextual factors that influence achievement of desired outcomes.